Paleointensity study of late Miocene igneous rocks from British Columbia, Canada - Symons, D. T. A.; Schwarz, E. J. (Canadian Journal of Earth Sciences, 1970)
Sixty-nine specimens representing 49 late Miocene (10–15 m.y. ago) basaltic lava flows and 4 associated gabbroic intrusive plugs were studied in an attempt to estimate the paleointensity of the earth's magnetic field in south-central British Columbia. The paleointensity determination was based on the comparison of the decay of natural remanent magnetism intensity with that of an artificial thermoremanent magnetism (H = 0.35 Oe) in progressively higher alternating demagnetizing fields (peak: 800 Oe). Only 22 of the 69 specimens were considered to yield reliable paleointensity determinations which give an estimated average equatorial intensity for the late Miocene earth's field of 0.18 Oe ± 0.11. This result agrees reasonably well with those from contemporaneous rocks from North America, Japan, and Iceland. Several low determinations with consistent, normal, or reversed remanence directions suggest that the intensity of the non-dipole components of the late Miocene earth's field must have been very small in the sampled area.